Association of TNF-α promoter polymorphism and Graves' disease: an updated systematic review and meta-analysis. Issue 2 (21st March 2018) - Tu, Yaqin; Fan, Guorun; Zeng, Tianshu; Cai, Xiong; Kong, Wen
Abstract : Graves' disease (GD) is a common autoimmune disorder with a genetic predisposition. Owing to the biological effect of tumor necrosis factor-α (TNF-α) on the thyroid gland and its gene location, TNF-α should be able to influence an individual's susceptibility to GD. In the present study, we conduct a meta-analysis of rs1800629 and rs361525 in TNF-α gene from all eligible case–control studies to assess the associations amongst reported TNF-α gene with GD. A total of ten case–control studies involving 2790 GD patients and 3472 healthy controls were included. The results showed that a significant association was characterized between the rs1800629 polymorphism and GD in the homozygous model (AA compared with GG: odds ratio (OR) = 1.97, 95% confidence interval (CI) = 1.27–3.06, P =0.002) and recessive model (AA compared with GA + GG: OR = 1.62, 95% CI = 1.04–2.50, P =0.03). GD susceptibility was significantly detected in European population in all genetic models after ethnicity stratification. In sharp contrast, no significant association could be detected in Asian population. Next, we conducted a meta-analysis for another promoter SNP rs361525. However, SNP rs361525 did not show a significant association with GD in any genetic model before and after ethnicity stratification. Together, our data support that only the promoter single-nucleotide polymorphism (SNP) rs1800629 within the TNF -α gene is associated with increased risk for developing GD, especially in European population. Future large-scale studies are required to validate the associations between TNF-α gene and GD.